Preparation of a fluorescent silver nanoprism–dye complex for detection of hydrogen peroxide in milk. Issue 23 (20th July 2015) - Peng, Chifang; Liu, Chunli; Xie, Zhengjun
Abstract : A simple and sensitive "turn-on" fluorescence detection method for H2 O2 in milk was developed based on H2 O2 induced morphology transitions of fluorescent dye–protein complex-capped silver nanoprisms (FDSNPs). Abstract : A simple and sensitive "turn-on" fluorescence detection method for H2 O2 in milk was developed based on H2 O2 induced morphology transitions of fluorescent dye–protein complex-capped silver nanoprisms (FDSNPs). The rounding of the FDSNPs accompanies desorption of a fluorescent dye–protein complex, which resulted in recovery of the fluorescence intensity. In a 4 order of magnitude dynamic range from 10 nM to 100 μM, the fluorescence intensity of the FDSNPs sensitively increased with increasing H2 O2 concentration. The limit of detection for H2 O2 was 4.0 nM. Furthermore, the developed method was applied to detect H2 O2 in milk with satisfying recoveries of over 80% after milk was simply pretreated.